Effect of SS316L Plate’s Surface Texture on Hydrogen Production of HHO Generator for Defence Application in Remote Locations - Sinurat, Michael Tulus Samuel; Ansori, Ansori; Aritonang, Sovian; Repi, Viktor Vekky Ronald; Ridhwan, Asmawi Marullah (Formosa Journal of Science and Technology, 2025)
The research aims to determine if surface texture of HHO generator’s electrode plate affect hydrogen production, and which of 4 tested surface textures gives the best performances. Electrolytes used is KOH with variation in concentration of 10, 20, 30, 40, 50, and 60 g/L. Testing is done by running the generator to produce 1 L of hydrogen, with the tested parameter being current, electrolytes temperatures, and time required. Data is measured in 2 waves: the first wave is 30 measurements with the generator always on, and the second wave is 30 measurements with the generator turned off for 10 seconds between measurements. The average, standard deviations, and correlation coefficients is compared to determine the best surface texture.